SOCIAL MEDIA KALEIDOSCOPE - Hajibayova, Lala; Buente, Wayne (AoIR Selected Papers of Internet Research, 2015)
This study investigates the case of Isa Shahmarli, an Azerbaijani LGBTQ activist, who committed suicide in January of 2014. Even though the subject of sexual minorities is taboo in conservative Azerbaijan (The Danish Institute of Human Rights, 2010), activist’s death was covered in the mass media and resulted in debate on the rights of the sexual minorities in Azerbaijan. This study analyzes the Facebook public page of the Azerbaijan Free LGBT Organization in response to the activist’s suicide.